Employment and poverty dynamics in the EU countries before, during and after the crisis - ImPRovE, Antwerp; Gábos, András; Branyiczki, Réka; Lange, Barbara; Tóth, István György (Antwerp, 2015)
"The paper aims to contribute to a better understanding of how employment change relates to changes in poverty in the European Union’s Member States by looking at both micro and macro level correlations. EU-LFS and EU-SILC data are used to analyse trends between 2005 and 2012, to reflect also on the societal effects of the financial and economic crisis. Time series for this period show that the crisis has resulted in very different employment trajectories. Larger volatility in employment was accompanied by a relatively sizeable change in poverty rates as well. According to our preferred regression model estimates, poverty to employment elasticity has been around 25 percent on average in the EU in the period between 2005 and 2012. The decomposition of poverty changes shows that countries differ greatly in the portion of total poverty changes attributed to changes in the poverty rates of both individuals living in jobless and non-jobless households, as well as in the portion of total poverty changes attributed to the changes in the population share of those in jobless households. We conclude that the success of poverty reduction depends to a large extent on three factors: the dynamics of overall employment growth, the fair distribution of the employment growth across households with different work intensity and properly designed social welfare systems to smooth out income losses for those families who are, for some reasons, unable to generate sufficient income for themselves from the labour markets."